Fever - Rosenberg, Noah (The Hastings Center report, 2015)
An earthy smell seeps from the cinderblock room, and a fan in the corner rattles as it circulates the heat. My eyes cross trying to read the square black numbers on the thermometer. I feel achy and tired. I would not be so nervous about the result except that I have been caring for Ebola patients in West Africa.